Mapping antibiotic resistance in Ghana: a narrative review of regional variations in antibiotic-resistant ESKAPEE pathogens - Abubakari, Abdulwasid; Agbeko, Rosemary; Osei-Adjei, George; Kümmerli, Rolf (Frontiers in Microbiology, 2026)
IntroductionAntibiotic resistance (ABR) is a global health crisis and a significant public health challenge in Ghana. This narrative review aims to uncover the patterned landscape of ABR by systematically assessing regional heterogeneity across three key dimensions: (1) the geographic distribution and intensity of ABR surveillance and research; (2) the prevalence of ESKAPEE pathogens (Enterococcus faecium, Staphylococcus aureus, Klebsiella pneumoniae, Acinetobacter baumannii, Pseudomonas aeruginosa, Enterobacter species, and Escherichia coli); and (3) the distribution of their antimicrobial resistance profiles and underlying genetic mechanisms. The review maps data from clinical, animal, and environmental sources to provide a comprehensive sub-national picture.MethodsFour online databases (PubMed, Scopus, Web of Science, and African Journals Online) were searched for relevant articles published from 2016 to 2025, a timeframe chosen to align with the development and implementation of Ghana’s first National Action Plan (NAP) on AMR (2017–2021). A narrative synthesis was conducted to collate, analyze, and map regional data on ESKAPEE pathogen prevalence, resistance patterns, and underlying genetic mechanisms.ResultsA total of 48 studies met the inclusion criteria. The findings reveal a significant disparity in research coverage, with a heavy concentration of studies in the Greater Accra (35.4%) and Ashanti (18.6%) regions. Widespread multidrug resistance was evident across all studied regions, with E. coli and K. pneumoniae consistently showing high resistance (>70%) to common antibiotics like ampicillin and third-generation cephalosporins. The review documents the emergence of critical carbapenemase genes (including blaNDM-1 and blaOXA-48), a notable prevalence of methicillin-resistant S. aureus (MRSA), and the detection of the colistin resistance gene mcr-1 in animal sources. Significant heterogeneity in study design and methodology was observed across the included literature.ConclusionABR in Ghana presents as a patterned landscape rather than a uniform national profile. Stark regional disparities and major surveillance gaps create “blind spots” that can hinder the effective implementation of national policy. Addressing this requires prioritizing surveillance in under-studied regions and standardizing methodologies. Furthermore, region-specific control strategies must be developed using a “One Health” approach, one that integrates surveillance and stewardship interventions across human healthcare, agricultural, and environmental sectors.